2013
DOI: 10.3945/ajcn.112.051383
|View full text |Cite
|
Sign up to set email alerts
|

Prospective associations between sugar-sweetened beverage intakes and cardiometabolic risk factors in adolescents

Abstract: Background: High sugar-sweetened beverage (SSB) consumption is associated with cardiometabolic disturbances in adults, but this relation is relatively unexplored in children and adolescents.Objective: We tested the hypothesis that higher SSB intakes are associated with increases in cardiometabolic risk factors between 14 and 17 y of age.Design: Data were provided by 1433 adolescent offspring from the Western Australian Pregnancy Cohort (Raine) Study. At 14 and 17 y of age, SSB intakes were estimated by using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
195
1
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(209 citation statements)
references
References 26 publications
(50 reference statements)
7
195
1
5
Order By: Relevance
“…Energy share from sugar exceeds the recommended 10 %, and children and adolescents consume an even higher energy share from sweets than adults (40,42) . There is evidence of the link between excessive intake of free sugars, especially through sugar-sweetened beverages, and overweight and NCD (44)(45)(46) . Although the high sugar intake is well known and problematic, the current study indicates that even more effort is needed on reducing intake of the sweet ultra-processed products that are the main vehicles for sugar intake.…”
Section: Implications For Healthmentioning
confidence: 99%
“…Energy share from sugar exceeds the recommended 10 %, and children and adolescents consume an even higher energy share from sweets than adults (40,42) . There is evidence of the link between excessive intake of free sugars, especially through sugar-sweetened beverages, and overweight and NCD (44)(45)(46) . Although the high sugar intake is well known and problematic, the current study indicates that even more effort is needed on reducing intake of the sweet ultra-processed products that are the main vehicles for sugar intake.…”
Section: Implications For Healthmentioning
confidence: 99%
“…Some short-term intervention studies found that high intakes of sucrose (6) or fructose (7,8) appear to reduce insulin sensitivity, whereas others failed to show such effects (9,10). Conflicting findings have also emerged from observational studies that examined habitual intakes of different types or sources of sugars and HOMA-IR in adults (11)(12)(13)(14) and children (15)(16)(17). Furthermore, to our knowledge, few studies have examined the longterm association between SSB intake and the incidence of prediabetes, separately from T2D, in healthy adults.…”
Section: Introductionmentioning
confidence: 89%
“…In 2 studies under-reporters were included in the analysis but with adjustment for underreporting, and in 4 studies under-reporters were excluded. Five studies used BMI as body weight outcome [20,21,22,23,24], 5 BMI Z-score [25,26,27,28,29], 3 body fat [30,31,32], 3 waist circumference [33,34,35], and 1 weight-for-height z-score [36] (table 1). Almost all (94%) of the articles showed a positive association between SSB intake and body weight measures, meaning that a higher SSB consumption lead to a higher degree of adiposity.…”
Section: Resultsmentioning
confidence: 99%